APOE genotyping and its association with cognitive deficits in children with diarrhea and malnutrition in the Northeast-Brazil - Reinaldo Barreto OriÃ (2004)
Polymorphisms in the apolipoprotein E (APOE) have constituted the major rationale to identify potential risk groups for developing late-onset Alzheimer's disease and help to predict recovery of cognitive function after brain injury. However, the APOE impact on cognitive development in children living in poor areas of the developing world, where we have discovered profound significant associations of early childhood diarrhea (at 0-2 yo) with lasting impairments of growth, cognition and school performance, is not known. Therefore, we conducted APOE genotyping in 72 Brazilian shantytown children under active surveillance since birth, using purified DNA extracted from buccal cell samples. We found a high frequency of APOE4 alleles (18% vs 9-11% expected) in children with lower diarrhea burdens. When we examined the children who experienced the heavier diarrhea burdens (+/- median of 7 illnesses in the first 2 years of life), those with APOE4 did significantly better in the coding subtest (39 +/- 9.9; n=7, p=0.01), when compared with APOE4 negative children with similar diarrhea burdens (25 +/- 12.7; n=27). Positive correlations between the APOE4 occurrence and coding scores remained even after adjusting for family income, maternal education and breast-feeding (p<0.05). Moreover, the APOE4 positive group, under heavy burdens of diarrhea, preserved semantic fluency and the mean difference in fluency scores (DIFF), n=73, p=0.025, a standardized coefficient for disproportional verbal fluency impairment. Our findings show that APOE4 is relatively common in children from the GonÃalves Dias Community in the Northeast Brazil and suggest a protective role of APOE4 allele in children with a history of heavy burdens of diarrhea in their first 2 years of life.